Influence of folic acid on birthweight and growth of the erythroblastotic infant. I. Birthweight. - Gandy, G (1977)
The birthweights of 100 infants with erythroblastosis were carefully matched as to sex, gestational age, and parity with the birthweights of 200 control infants born during the same period. At all gestational ages the average birthweight of the affected infants was below that of the controls, the average reduction being 227 g. The more severely affected infants tended to be at a lower centile for birthweight than were the mildly affected ones. The relationships between maternal serum folate, cord blood serum folate, and centile for birthweight among affected infants were also studied. There was a strong correlation between low maternal serum folate and the incidence of small-for-dates babies among the affected infants. There was also a strong correlation between maternal and cord blood serum folate values. There was a lack of correlation between maternal serum folate and cord blood haemoglobin. It is concluded that infants with erythroblastosis are lighter than controls and that the reason for this may be a shortage of folic acid available for fetal growth.